ERS/EAACI statement on severe exacerbations in asthma in adults: facts, priorities and key research questions. Issue 3 (28th September 2019) - Bourdin, Arnaud; Bjermer, Leif; Brightling, Christopher; Brusselle, Guy G.; Chanez, Pascal; Chung, Kian Fan; Custovic, Adnan; Diamant, Zuzana; Diver, Sarah; Djukanovic, Ratko; Hamerlijnck, Dominique; Horváth, Ildikó; et al.
Despite the use of effective medications to control asthma, severe exacerbations in asthma are still a major health risk and require urgent action on the part of the patient and physician to prevent serious outcomes such as hospitalisation or death. Moreover, severe exacerbations are associated with substantial healthcare costs and psychological burden, including anxiety and fear for patients and their families. The European Academy of Allergy and Clinical Immunology (EAACI) and the European Respiratory Society (ERS) set up a task force to search for a clear definition of severe exacerbations, and to also define research questions and priorities. The statement includes comments from patients who were members of the task force. ERS/EAACI statement on severe exacerbations in asthma in adults http://bit.ly/2Hl8sqf